Usability test of a hand exoskeleton for activities of daily living: an example of user-centered design. (2nd January 2017) - Almenara, Maria; Cempini, Marco; Gómez, Cristina; Cortese, Mario; Martín, Cristina; Medina, Josep; Vitiello, Nicola; Opisso, Eloy
Abstract: Purpose : (1) To assess a robotic device (Handexos) during the design process with regard to usability, end user satisfaction and safety, (2) to determine whether Handexos can improve the activities of daily living (ADLs) of spinal cord injury (SCI) patients and stroke patients with upper-limb dysfunction. Methods : During a 2-year development stage of the device, a total of 37 participants (aged 22–68), 28 clinicians (experts) and nine patients with SCI or stroke (end users) were included in a user-centered design process featuring usability tests. They performed five grasps wearing the device. The assessments were obtained at the end of the session by filling out a questionnaire and making suggestions. Results : The experts' opinion was that the modified device was an improvement over the preliminary version, although this was not reflected in the scores. Whereas end user scores for comfort, grasp, performance and safety were above the sufficiency threshold, the scores for year 2 were lower than those for year 1. Conclusions : The findings demonstrate that although Handexos meets the initial functional requirements and underlines the potential for assisting SCI and post-stroke subjects in ADLs, several aspects such as mechanical complexity and low adaptability to different hand sizes need to be further addressed. Implications for Rehabilitation: Wearable robotics devices could improve the activities of daily living in patients with spinal cord injury or stroke. They could be a tool for rehabilitation of the upper limb. Further usability tests to improve this type of tools are recommended.